Investigations on the risk factors of Acute Respiratory Infections (ARIs) among under-five children in Depok City, Indonesia - Wulandari, R.A.; Fauzia, S.; Kurniasari, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. Acute Respiratory Infections are caused by pathogens that spread rapidly. Acute Respiratory Infections include upper respiratory tract infections and lower respiratory tract infections. According to the World Health Organization (2019), Acute Respiratory Infections rank fourth among diseases that affect children with high morbidity. Indonesia’s under-five mortality rate due to Acute Respiratory Infections rank first among the Association of Southeast Asian Nations. Under-five mortality due to Acute Respiratory Infections in Indonesia accounts for 22.30% of the total under-five mortality cases. Study design and methods. This cross-sectional study was conducted with a total of 100 mother and child pairs selected by simple random sampling. Internal and external factors, including nutritional status, maternal age, maternal education level, presence of a smoker in the house, house ownership, household size, temperature, humidity, lighting, ceilings, floors, walls, and ventilation were investigated as the risk factors of Acute Respiratory Infections among under-five children in this study. Results. Our cross-sectional study found that 68 out of 100 under-five children in this study were infected with Acute Respiratory Infections during the study period. Among the risk factors, our multivariate analysis suggests that presence of smokers, maternal age, and inadequate ceiling conditions were the potential determinants of Acute Respiratory Infections among under-five children in Depok City. Conclusions. Despite the limitations of this study, we believe our results could give a comprehensive overview of the risk factors of Acute Respiratory Infections in under-five children